Guideline for Human Resource Development of Chef in Restaurant Business - Piyachokphaisarn, Sucharat; Kasai, Praweena (Dusit Thani College Journal, 2022)
This research aims to study 1) the demand in self-development of the kitchen staff from the Copper Buffet Restaurant, 2) problems in developing the kitchen staff, and 3) the development strategies of the kitchen staff. To collect the data, the questionnaire was distributed to 60 Copper Buffet kitchen staff who have at least 1 year of work experience, and the interview was conducted to a manager and 2 human resource managers. The statistics used in the data analysis are percentage, mean, standard deviation, independent t-test and one-way ANOVA. The results showed that the overall demand for the development of the kitchen staff is at a medium level: The kitchen staff development in terms of training is at a medium level, while the highest average score item is an informative lecture on the job description, supervisor, one-on-one training, and flexibility to learn other kitchen stuff; The overall demand for kitchen staff development in terms of education is at a low level, while the highest average score item is receiving specialized training to develop work proficiency; The overall demand for kitchen staff in terms of development is at a low level, while the highest average score item is field trip, followed by the assignment of new challenging tasks. Problems in the development of kitchen staff are at a medium level. The most problematic one is the organization lacking a training department, followed by lecturers having no expertise, knowledge, and skills to provide education to the staff. For the development strategies of the kitchen staff, Copper Buffet Restaurant is managed with highly values personnel development. The employees must have an opportunity to learn both theory and practice which they can practically perform and work across departments in the kitchen.